2016
DOI: 10.15537/smj.2016.5.13872
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of non-transported emergency medical services calls in Saudi Arabia

Abstract: Objectives:To determine the epidemiology of non- transported emergency medical services (EMS) calls within the EMS system at Riyadh, Saudi Arabia, to identify factors that contributes to non-transport of patients by EMS provider, and to recommend suggestions for reduction in number of non-transported calls.Methods:Retrospective analysis of 1390 patient care reports (PCR) of non-transported cases responded to, and documented by the Saudi Red Crescent Authority (SRCA) emergency medical technicians (EMTs). All PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 10 publications
1
36
0
Order By: Relevance
“… 34 Another study by Alrazeeni et al examined nontransported EMS calls and found 65% had a 15-minute response time and 17% had up to a 30-minute response time. 35 Studies from other countries reported a shorter response time. A study from Iran showed most EMS calls were delivered within 8 minutes, 36 while in Beijing the median response time was about 16.5 minute.…”
Section: Discussionmentioning
confidence: 98%
“… 34 Another study by Alrazeeni et al examined nontransported EMS calls and found 65% had a 15-minute response time and 17% had up to a 30-minute response time. 35 Studies from other countries reported a shorter response time. A study from Iran showed most EMS calls were delivered within 8 minutes, 36 while in Beijing the median response time was about 16.5 minute.…”
Section: Discussionmentioning
confidence: 98%
“…Non-transport can occur because patients refuse to go to hospital or because ambulance clinicians make decisions not to take patients to a hospital. In some countries refusal to travel is the main reason for non-transport (sometimes called non-conveyance),[ 1 ] but in other countries ambulance services have policies and guidelines to allow staff to make decisions about whether to transport patients to hospital. [ 2 ] Non-transport rates vary by country and research study.…”
Section: Introductionmentioning
confidence: 99%
“…While formal evaluation of training quality is yet to be conducted, several challenges have been identified in the literature, including students' perceived lack of confidence, trust, and independence, 5 and deficits in EMS coverage of some geographical locations. 6 Additionally, EMT trainees continue to face such societal challenges as refusal of treatment by patients and/or relatives, 5,7 scene congestion caused by bystanders, 5 and the high prevalence of cancelled emergency calls. 7 Until identified challenges are addressed, immediately available resources ought to be prioritized with the goal of producing competent, Saudi-trained EMTs.…”
mentioning
confidence: 99%